PcWRKY1 Represses Transcription of Yellow Stripe‐Like 3 (PcYSL3) to Negatively Regulate Radial Cadmium Transport in Poplar Stems - Xin Chen; Yuhong Zhang; Yao Cheng; Wenjian Yu; Lingyu Yang; Peiqi Shu; Jing Zhou; Payam Fayyaz; Zhi‐Bin Luo; Shurong Deng; Wenguang Shi (Advanced Science)
Abstract A considerable amount of cadmium (Cd) can accumulate in the bark of poplar stems, but the Cd transport pathway and its underlying molecular mechanisms remain unknown. Here, a Cd radial transport pathway in poplar stems and a previously unrecognized PcWRKY1‐Yellow Stripe‐Like 3 (PcYSL3) module that regulates Cd transport are identified in Populus × canescens (Aiton) Sm. Cadmiun‐nicotianamine (Cd‐NA) in xylem vessels in poplar stem‐wood is unloaded to adjacent ray parenchyma cells and further radially transported to bark‐phloem. PcYSL3 is putatively identified as involved in Cd radial transport in poplar stems. PcYSL3 is highly expressed in ray parenchyma cells adjacent to xylem vessels and the encoded protein localizes on the plasma membrane. Cd accumulation is greater in the wood and bark of PcYSL3‐overexpressing poplars than the wild type, whereas the opposite is observed in PcYSL3‐knockdown plants. PcWRKY1 can bind to the PcYSL3 promoter sequence and represses its expression. PcWRKY1 inhibits Cd accumulation in the wood and bark of plants. Thus, PcWRKY1 suppresses PcYSL3 transcription to negatively regulate Cd‐NA unloading from xylem vessels to adjacent ray parenchyma cells and its radial transport in poplar stem. The findings have provided new insights into breeding of poplars for more effective remediation of heavy metal‐contaminated soils.